Structure & composition of carbon fibers for electrochemical applications - Schilling, Monja; Vocht, Marc P.; Debastiani, Rafaela; Scherer, Simon; Hermanutz, Frank; Zeis, Roswitha (Journal of Power Sources, 2025)
Carbon-based electrode materials are used in a broad range of energy storage systems and influence their performance significantly. Electrode materials must be investigated to optimize the technologies' efficiency. This study examines lab-fabricated and commercial electrode materials for vanadium redox flow batteries (VRFBs), and the influence of thermal treatment on these materials. Scanning electron microscopy images and X-ray nano-computed tomography revealed significant differences between the 3D shapes of the carbon fibers, which are influenced by the choice of precursor material and manufacturing process. Both have a crucial influence on the inner structure of the fibers, such as holes, which lower the mechanical stability. Furthermore, the composition of the fibers was assessed using wide-angle X-ray scattering and X-ray photoelectron spectroscopy highlighting especially differences in the fibers' oxygen- and carbon content. The applied thermal treatment increased the O-content and thus enhanced the material's wettability, which was investigated with dynamic vapor sorption. No structural changes in the fiber shape were monitored after thermal treatment. The materials' electrochemical performance was studied for VRFBs. The study of different electrode materials here shows the importance of choosing a suitable precursor and manufacturing process and the need for a multimodal characterization of materials to identify potential candidates.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Carbon-based electrode material; Manufacturing of carbon fibers; Thermal activation; Vanadium redox flow battery; X-ray nano-computed tomography